Systematic Literature Review: Penerapan Software Geogebra Terhadap Kemampuan Berpikir Matematis (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2023)
This study aims to conduct a qualitative study of the result of previous research related to the application of geogebra software to mathematical thinking skills in the 2018-2023 time frame. The research method uses systematic literature review (SLR) assisted by publish or perish software in the article search using the PRISMA protocol. The moderator variables in this study include the year published, level of education, research location, material, journal index, and type of mathematical thinking ability. The data is presented in a quantitative descriptive manner. The results showed that: 1). The distribution of studies on the application of geogebra to mathematical thinking skills is presented in the period 2022-2023, 2) The research location is dominated by Java, 3) The most widely used materials are derivatives, linear programs, and geometry, 4) The type of mathematical thinking ability that is widely studied is the ability to think creatively. Next, educators and researchers should research more on aspects of elementary school education level, materials other than derivatives, linear and geometry programs, and conduct more research outside Java. Regarding mathematical thinking skills, it is advisable to review logical and spatial thinking skills. Keywords: Geogebra; Mathematical thinking skills; Moderating variables; PRISMA protocol; Systematic literature review.